Сравнительная характеристика головного мозга некоторых насекомоядных и рукокрылых - Омельковец, Я.И. (Вестник зоологии, 1993)
Macromorphological brain differences between certain Insectivora and Chiroptera are outlined after angular dimensions arid relative indices. An attempt of an analysis is given.